ANALISIS KONSISTENSI PERENCANAAN DAN PENGANGGARAN DI KABUPATEN PEGUNUNGAN BINTANGSTUDI KASUS PADA DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA TAHUN 2013-2015 - Alferus Sanuari; Yundy Hafizrianda; Siti Rofingatun (Universitas Cenderawasih, 2017)
This research entitled Analysis of Planning and Budgeting Conceptency in Pegunungan Bintang District Case Study On Department of Transportation, Communication and Informatics Year 2013-2015. In this research try to analyze consistency between planning and budgeting seen from planning and budgeting document like RKPD, PPAS, and APBD. RKPD (Local Government Work Plan), which is the result of the selection of community aspirations through the Development Planning Council (Musrenbang). Furthermore, RKPD work plan and funding are used as guidance in the budgeting process (budgeting). Budgeting begins with the preparation of Temporary Budget Priorities and Ceiling (PPAS). The approved PPAS is used as a guideline for the preparation of Regional Revenue and Expenditure Budget Plans (RAPBD) which is then ratified into Regional Revenue and Expenditure Budget (APBD). The results of the analysis are then analyzed using the Planning and Budgeting Consolidation Matrix to see how far the consistency is occurring. The results of this study indicate that the average level of consistency planning and budgeting in the field of Transportation, Communications and Informatics in Pegunungan Bintang District in 2013-2015 is quite good where the average level of consistency of programs between RKPD and PPAS ranges between 80.00%. While the average level of consistency of activities is 61.98%. This indicates that the drafting of the plan on PPAS still exists that is not guided by RKPD. The level of program consistency between PPAS and APBD has an average value of 60.64%. While the average level of consistency of activity is 63.19%. The level of planning and budgeting concessions from year to year shows a fluctuating value. In consistency the budget outline has a consistent value. Inconsistencies occur because there are activities that suddenly appear and are not contained in the previous document. This is due to delays in information activities from the central government. Keywords: Consistency, Planning, Budgeting